2013
DOI: 10.3390/ijms141223289
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Evaluation of Tyrosine Hydroxylase Inhibition in Planaria as a Model for Parkinsonism

Abstract: Planaria are the simplest organisms with bilateral symmetry and a central nervous system (CNS) with cephalization; therefore, they could be useful as model organisms to investigate mechanistic aspects of parkinsonism and to screen potential therapeutic agents. Taking advantage of the organism’s anti-tropism towards light, we measured a significantly reduced locomotor velocity in planaria after exposure to 3-iodo-l-tyrosine, an inhibitor of tyrosine hydroxylase that is an enzyme catalyzing the first and rate-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
4
2
Order By: Relevance
“…In another study, bromocriptine, a drug used for the treatment of Parkinson's disease in humans, was added to the water of planarians at the 10 n m concentration and behavioral differences were observed. The movements were noted to slow down and C‐like hyperkinesia was observed . In our study, such anomalies were not observed in early times (between days 3 and 8).…”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation
“…In another study, bromocriptine, a drug used for the treatment of Parkinson's disease in humans, was added to the water of planarians at the 10 n m concentration and behavioral differences were observed. The movements were noted to slow down and C‐like hyperkinesia was observed . In our study, such anomalies were not observed in early times (between days 3 and 8).…”
Section: Resultscontrasting
confidence: 47%
“…The movements were noted to slow down and C-like hyperkinesia was observed. [38] In our study, such anomalies were not observed in early times (between days 3 and 8). The experimental group showed convulsion-like behavior upon light exposure on day 13, yet only in the tail pieces they regenerated a new brain.…”
Section: The Effects Of Free and Encapsulated Tq On Planarians As A Mcontrasting
confidence: 53%
“…Planarians prefer darkness and use photoreceptors to detect and react to light. As such, planarians are capable of maze learning and can develop a conditioned response to light that can be implemented in behavioral studies including those subject to drug modification [ 40 , 41 ]. Planarian motility assays have also been developed for studies examining substance addiction and withdrawal [ 42 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In This review we attempted to show some important aspects of planarian characteristics make this animal an extraordinary model for regenerative medicine researches. On the other hand a variety of genes and signaling molecules conserved between this animals and higher vertebrates as well as human makes this animal a good model for study about diseases as well as Parkinson ( 33 ) and may provide new ideas for handling mouse and human ES cells for therapeutic use in the near future ( 34 ).…”
Section: Discussionmentioning
confidence: 99%